The determinant of foreign exchange reserves in Asian countries / Nur Syafiza Roslan - Roslan, Nur Syafiza (Faculty of Business and Management, 2018)
The paper investigates the relationship between Foreign Exchange Reserves (FER), Import (1M), Current Account Balance (CA) and Gross Domestic Product (GDP) in Asia Countries. It has been observed that most developing countries of Asia since the Asia Crisis Of 1997 have engaged in massive accumulation of Foreign Exchange Reserves. The accumulation has been done regardless of the economic implication on the macroeconomy. Econometric evidence shows that the variables in the study have least square method. The results of the tests show that Current Account Balance, GDP and Import have positive and significant relationship With FER. Asia countries are accumulating FER because of her over dependent on imports but should aware of the social costs implication. Proper management of reserves is recommended.